Tinjauan Hukum Terhadap Peraturan Menteri Agraria Dan Tata Ruang/Kepala Badan Pertahanan Nasional (PERMEN ATR/BPN) Nomor 1 Tahun 2021 Dan Pasal 19 Ayat 2 UUPA - Heriyanti Heriyanti; Sandi Noel Rajagukguk; Samuel Sitinjak; Elvira Fitriyani Pakpahan (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
So it very well may be gathered that the land enlistment action interestingly brought about a declaration of confirmation of rights as an authentication of land allocates as of now have rights and a testament of proprietorship rights to condo units. Revelation is a validation of proof of rights as implied in Article 19 Paragraph (2) letter c of the UUPA for land rights, the chiefs rights, waqf rights, property rights over space units and security rights, all of which has been recorded in the land book concerned. ATR/BPN 1/2021 specifies that the execution of land enrollment which incorporates land enlistment interestingly and upkeep of land enlistment information should be possible electronically which will later be for this situation, the execution of land enrollment like estimating, planning, and clearing is as yet dependent on Article 19 section 2 of the UUPA, just the authoritative land enrollment testament delivered alludes to Permen ATR/BPN Number 1 of 2021 so this electronic land authentication doesn’t cancel or supplant the capacity of customary land endorsement (paper) which can likewise be a legitimate lawful proof of land proprietorship in the legal interaction. Both electronic and traditional testaments have a similar situation under the watchful eye of the law or can turn out to be lawfully substantial proof dependent on Article 5 passage 2 of the ITE Law.